Proceso atención de enfermería en paciente de 45 años con neumonía asociada a Covid 19. - Valle Cedeño, Johnny Cesar (2021)
The present clinical case was carried out at the Dr. José Cevallos Ruiz de Yaguachi Basic Hospital, it belongs to a 45-year-old male patient, admitted to the emergency area of the hospital unit accompanied by a family member, conscious and oriented, presenting a clinical picture of ± 72-hour evolution characterized by hypertemia, dry cough, dyspnea, general malaise, fatigue, semi-solid to liquid stools, tachycardia, tachypnea, oxygen saturation 92%, anosmia, dehydrated mucosa, added breath sounds, wheezing, muscle weakness, proceed to work on the nursing care process, starting the assessment through the physical examination and complementary examinations, having as a definitive diagnosis Pneumonia associated with COVID 19 entering the isolation area to receive the respective treatment and nursing care, in addition to emphasizing Dorothea's theorizing Orem of self-care deficit to improve patient care in order to make it participate in the process of recovering their health, peripheral venous access channeling is carried out, drug administration according to medical indications, oxygen therapy by nasal cannula, thermal curve, water balance, low sodium diet, postural changes, application of physical means and nursing care.